A closer look at gender and Arabic language learning strategies use - Mat Teh, Kamarul Shukri; -, Embi; -, Yusoff; -, N.M.R.N.b (2009)
Numerous studies have discerned gender differences in language learning strategies (LLS) use. In most of the studies in which gender differences emerged, the results showed that female reported using language learning strategies more often than males. However, some studies demonstrated that there was no statistically significant difference between gender in the use of LLS. Others showed that male students use more LLS than female students in certain categories. Therefore, the purpose of this study was to investigate whether or not differences exist between female and male Arabic students in the use of language learning strategies. A total of 457 students at thirteen secondary schools in Terengganu, Malaysia participated in the study. Data was collected using a questionnaire adapted and modified from SILL (Oxford 1990). The findings of the study showed that there was significant gender difference in the use of language learning strategies as a whole. Female students also tend to use overall language learning strategies more often than males. For categories of language learning strategies, there are significant differences between genders in the use of affective and metaphysic strategies with females using them more often.